2016
DOI: 10.1177/1591019915622164
|View full text |Cite
|
Sign up to set email alerts
|

Ten years of experience in endovascular treatment of ruptured aneurysms of the posterior inferior cerebellar artery

Abstract: Background The aim of this study is to present our 10 years of experience in endovascular treatment of ruptured posterior inferior cerebellar artery (PICA) saccular aneurysms and to compare clinical presentation and outcome after endovascular treatment between patients with PICA aneurysms and patients with aneurysms in different locations. Methods and findings Out of 932 patients with a ruptured intracrani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 46 publications
0
7
0
1
Order By: Relevance
“…A meta-analysis suggested PICA aneurysms treated with EVT had a higher recurrence rate and lower occlusion rate than those treated with surgery 35 . Robert et al also reported 29.4% of the patients who underwent EVT required retreatment due to aneurysm recurrence 72 . The safety and efficacy of EVT still need to be improved.…”
Section: Aneurysmmentioning
confidence: 98%
“…A meta-analysis suggested PICA aneurysms treated with EVT had a higher recurrence rate and lower occlusion rate than those treated with surgery 35 . Robert et al also reported 29.4% of the patients who underwent EVT required retreatment due to aneurysm recurrence 72 . The safety and efficacy of EVT still need to be improved.…”
Section: Aneurysmmentioning
confidence: 98%
“…60,63,[65][66][67] The endovascular retreatment rate for VA and PICA aneurysms was reported around 20%e30%. 58,68 A recent comparative study between clipping and coiling in 102 patients with VA and PICA aneurysm 69 did not show any significant difference in the patients' clinical outcomes. Our results compare favorably with these endovascular results.…”
Section: Endovascular and Microsurgery Perspectivementioning
confidence: 96%
“…Ayrıca bu bölgede zengin perforanların bulunması gerek cerrahi gerekse endovasküler tedavide güçlükler oluşturur. Özellikle disekan olan anevrizmaların ayırt edilmesi, bunların tedavisinde farklı yaklaşım gerekmesi nedeniyle önemlidir [4,[10][11][12].…”
Section: Gereç Ve Yöntemlerunclassified